Prática interdisciplinar no curso de Letras-Libras UFAM: um olhar sobre o ensino-aprendizagem dos acadêmicos surdos - Lima, Cristina dos Santos (Brasil, 2024)
The main objective of this research was to identify how interdisciplinary practices are thought of by the faculty of the Literature Course - Libras at Ufam. Aware that the Letters-Libras course has both deaf and hearing students in its academic environment, and that the use of teaching strategies is very important. The concern for this research was limited to the 6th period of the LSB 007 class, which during this period used Interdisciplinary Teaching as a teaching strategy for an evaluative exercise. For Lück (2013) “Interdisciplinarity is the process that involves the integration and engagement of educators, in a joint work of interaction between the subjects of the school curriculum among themselves and with reality”. In this, three disciplines were involved: Didactics and Assessment in Deaf Education; Methodology for Teaching Literature in Libras and Methodology for Teaching Libras as L1. The research is of a qualitative nature which, according to Gerhardt; Silveira (2009) “qualitative research is not concerned with numerical representation, but rather with deepening the understanding of a social group, an organization, etc”. The research sample included the participation of three teachers and five deaf students. Questionnaires were administered via link, Google forms, with open questions asked in Portuguese and Libras. Data analysis was concerned with a careful analysis of the data collected, which Gil (2002) tells us that “many field studies enable statistical data analysis, especially when they use questionnaires or forms for data collection”. Therefore, the clear understanding that the interdisciplinary teaching strategy achieved its objective with deaf students, even though it was an initially difficult and challenging activity, which was made very evident during the research, managed to achieve success in the elaboration of the proposed evaluation exercise, which resulted in Finally, the preparation of a lesson plan and the recording of a video lesson lasting an average of 20 minutes.